Alokasi Biaya Penggunaan Pestisida untuk Pengendalian Hama Tanaman Kelapa Sawit pada PT Fajar Agung Kebun Bengabing Tahun 2021 - Sari Wahyuni; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the costs of using pesticides for pest control on oil palm plantations of PT. Fajar Agung-Kebun Bengabing during 2021. The use of pesticides in this study used several types of pesticides, including cypertop insecticide, agristick insecticide, marshal, royal cyper insecticide, acemain, metavaria, clerat, rogate insecticide, bestox insecticide, galastick insecticide, josefat, and insecticide rajapromotri. The data used in this study were primary data. The data analysis method in this study is described descriptively which is presented to describe or illustrate the data collected using tables. And based on the findings of this study, it can be concluded that the cost of using pesticides in 2021 will decreased due to pest attacks also decreasing. And it was found that the highest cost of using pesticides for pest control incurred by the company was the cost of using royal cyper insecticides, while the lowest cost was the use of cleric pesticides.